Muscle action potential scans and ultrasound imaging in neurofibromatosis type 2. Issue 3 (16th December 2016) - Farschtschi, Said; Gelderblom, Mathias; Buschbaum, Sabriena; Bostock, Hugh; Grafe, Peter; Mautner, Victor F.
ABSTRACT: Introduction: The neuropathy in patients with neurofibromatosis type 2 (NF2) is difficult to quantify and follow up. In this study we compared 3 methods that may help assess motor axon pathology in NF2 patients. Methods: Nerve conduction studies in median nerves were supplemented by deriving motor unit number estimates (MUNEs) from compound muscle action potential (CMAP) scans and by high‐resolution ultrasound (US) peripheral nerve imaging. Results: CMAP amplitudes and nerve conduction velocity were normal in the vast majority of affected individuals, but CMAP scan MUNE revealed denervation and reinnervation in many peripheral nerves. In addition, nerve US imaging enabled monitoring of the size and number of schwannoma‐like fascicular enlargements in median nerve trunks. Conclusion: In contrast to conventional nerve conduction studies, CMAP scan MUNE in combination with US nerve imaging can quantify the NF2‐associated neuropathy and may help to monitor disease progression and drug treatments. Muscle Nerve 55 : 350–358, 2017